2017
DOI: 10.22555/joeed.v4i2.1252
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Behaviour in High- Performing Government Boys Secondary Schools in Quetta: A Grounded Theory Analysis

Abstract: The performance of schools is highly dependent on the leadership of school heads, and, flexible leaders accelerate school performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The finding that interpersonal relationship leadership practice had a positive and significant relationship with students' discipline agreed with the findings of previous schools. In agreement, Bahadur et al (2017) established that relation-oriented leadership behaviours contributed to school performance, including students' discipline. Also, Rajbhandari et al (2016) reported that relationsoriented behaviours led to the development of schools, including modelling students' discipline.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The finding that interpersonal relationship leadership practice had a positive and significant relationship with students' discipline agreed with the findings of previous schools. In agreement, Bahadur et al (2017) established that relation-oriented leadership behaviours contributed to school performance, including students' discipline. Also, Rajbhandari et al (2016) reported that relationsoriented behaviours led to the development of schools, including modelling students' discipline.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, in a school where there are good interpersonal relationships, teachers will work hard to promote students' discipline. In their study done in high-performing schools in Quetta in Pakistan, Bahadur et al (2017) and Rajbhandari et al (2016) in a study involving Finnish schools reported that relation-oriented leadership contributed to school performance including students' discipline. In a study involving Kenyan schools, Kasivu (2020) found out that interpersonal relationships had a significant positive relationship with levels of students' discipline in public secondary schools.…”
Section: Interpersonal Relationships and Student Disciplinementioning
confidence: 99%